Quality of life and associated factors among people with epilepsy in Ethiopia: a systematic review and meta-analysis - Fantahun Andualem; Mamaru Melkam; Gebrieslassie Tadesse; Girum Nakie; Techilo Tinsae; Setegn Fentahun; Gidey Rtbey; Girmaw Medfu Takelle; Berihun Agegn Mengistie; Getachew Muluye Gedef (BMC, 2024)
Abstract Background Epilepsy is a global health and economic burden with major problems that have an impact on physical, psychological, and social activities. Quality of life (QoL) is often disturbed and can be influenced by many factors, like anti-seizure medication side effects, the sociocultural environment, and various disease-related factors. The aim of this systematic review and meta-analysis is to provide an overview of the most recent information available regarding the pooled prevalence of poor quality of life and associated factors among adult people with epilepsy in Ethiopia. Methods The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) is an appropriate set of guidelines for reporting systematic reviews and meta-analyses. This systematic review and meta-analysis protocol was registered on the International Prospective Register of Systematic Reviews (PROSPERO) with CRD42024527914. To find publications for the systematic review and meta-analysis, we used both manual and electronic searches. The publications were searched by PubMed, MEDLINE, EMBASE, Cochrane Library, Scopus, and other grey publications were searched by Google Scholar. The Joanna Briggs Institute (JBI) for cross-sectional study quality assessment was employed to evaluate the methodological quality of the studies included in this review. The data was extracted in Microsoft Excel, and then it was exported into STATA 11.0 for analysis. A funnel plot and an objective examination of Egger's regression test were used to check for publication bias. Results We have included 7 studies conducted in Ethiopia with 2123 study participants, of whom 1163 (54.78%) were male individuals, and 1196 (56.34%) of the participants were living without marriage (either single, divorced, or widowed). The pooled prevalence of poor quality of life among people with epilepsy in Ethiopia is 45.07 (95% CI: 39.73-50.42%). Further, in subgroup analysis regarding the assessment tool of poor quality of life of people with epilepsy, QOLIE-31 accounted for 50.05% (95%CI: 46.65-53.45) and WHO QOL BREF accounted for 39.72% (95%CI: 27.67-51.78). Among the associated factors, being unable to read and write, anxiey and depression were significantly linked to the quality of life of people with epilepsy. Conclusion This review found that there was a high pooled prevalence of poor quality of life related to people with epilepsy in Ethiopia. This study may provide further information to concerned bodies that do early screening and manage the quality of life of individuals with epilepsy. Also, screening and intervention for anxiety and depression problems should be considered in regular epilepsy care management.